ANALISIS TINGKAT KESEHATAN KOPERASI PADA KOPERASI KARYAWAN DJITOE SURAKARTA - Suharno, Anggrahini S. Dewi, Bambang Widarno & (Universitas Slamet Riyadi, 2016)
In this era of globalization, competition in the economy tends more and more strict. Likewise with the economic actors, especially cooperatives, especially on the financial performance of cooperatives that are required for rapid response in the decision to prevent the loss of profit opportunities exist or will otherwise incur losses for the cooperative. In connection with this, cooperatives must be more resilient in the face of change and competition that occurs in the environment the cooperatives themselves or compete with other non-bank financial institutions, nationally, regionally, and internationally. This research is aimed to determine the level of health of Employees Cooperative Djitoe Surakarta by using the rules of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 14 / Per / M.KUKM / XII / 2009. In this study, the authors used data from 2012 to 2014 year. Of the seven aspects of the cooperative health assessment, a score soundness Cooperative Employees Djitoe Surakarta overall got a score of 67.88, which means the Cooperative Employees belonging to cooperative Djitoe Surakarta pretty healthy.Keywords: Performance, aspect of capital, aspect of productif, aspect of management, aspect of liquidity, regulations Number: 14/Per/M.KUKM/XII/2009